Physicochemical, Antioxidant, Organoleptic, and Anti-Diabetic Properties of Innovative Beef Burgers Enriched with Juices of Açaí (Euterpe oleracea Mart.) and Sea Buckthorn (Hippophae rhamnoides L.) Berries - Anna Wojtaszek; Anna Marietta Salejda; Agnieszka Nawirska-Olszańska; Aleksandra Zambrowicz; Aleksandra Szmaja; Jagoda Ambrozik-Haba (Foods)
Background: The aim of this study was to evaluate the selected quality parameters of innovative beef burgers produced with the addition of açaí and/or sea buckthorn berry juices. Methods: Five variants of innovative burgers were obtained, differing in the proportion of juices in the recipe. The pH of meat stuffing, thermal losses, production yield, color (CIE L*a*b*), content of polyphenolic compounds, degree of oxidation of the lipid fraction (TBARS), and antioxidant activity against ABTS radicals were determined. Anti-diabetic activity was measured as the ability to inhibit α-glucosidase and dipeptidyl peptidase−4 activity. A sensory evaluation was also performed. Results: Beef burgers formulated with açaí and sea buckthorn juices had up to five times higher total polyphenol content than burgers without added juices. The addition of the juices increased antioxidant activity against ABTS radicals (from 42 to 440 µmol/L/100 g) and effectively inhibited oxidation of the lipid fraction of the beef burgers. Recipe modifications resulted in changes in the color parameters of the beef burgers and had a positive effect on the sensory quality attributes evaluated. Beef burgers containing 0.5 g of açaí juice and 1.0 g of sea buckthorn juice were rated the best in terms of acceptability of appearance, aroma, color, juiciness, and tenderness. The addition of açaí and sea buckthorn juice did not increase the inhibitory activity against α-glucosidase and dipeptidyl peptidase-IV of the innovative beef burgers. Conclusions: The proposed recipe modification may be an effective way to fortify beef burgers with phytochemicals with antioxidant properties while maintaining their sensory properties.